2014
DOI: 10.1105/tpc.114.130666
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis DE-ETIOLATED1 Represses Photomorphogenesis by Positively Regulating Phytochrome-Interacting Factors in the Dark

Abstract: Arabidopsis thaliana seedlings undergo photomorphogenic development even in darkness when the function of DE-ETIOLATED1 (DET1), a repressor of photomorphogenesis, is disrupted. However, the mechanism by which DET1 represses photomorphogenesis remains unclear. Our results indicate that DET1 directly interacts with a group of transcription factors known as the phytochrome-interacting factors (PIFs). Furthermore, our results suggest that DET1 positively regulates PIF protein levels primarily by stabilizing PIF pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
125
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(135 citation statements)
references
References 75 publications
4
125
0
Order By: Relevance
“…4D). Consistently, a recent study showed that DET1 interacted with and stabilized the PIF1 protein in etiolated seedlings (26). To illustrate the degradation dynamics of the PIF1 protein, we further performed a cell-free degradation assay.…”
Section: Det1 Genetically Acts Upstream Of Hfr1 and Pif1 In Repressinmentioning
confidence: 65%
“…4D). Consistently, a recent study showed that DET1 interacted with and stabilized the PIF1 protein in etiolated seedlings (26). To illustrate the degradation dynamics of the PIF1 protein, we further performed a cell-free degradation assay.…”
Section: Det1 Genetically Acts Upstream Of Hfr1 and Pif1 In Repressinmentioning
confidence: 65%
“…1). PIF1 and PIF3-5 are stabilized by DET1 in the dark 8 . These data suggest that the CUL4 COP1-SPA E3 ubiquitin ligase is involved in PIF1 degradation under these conditions, and that different PIF family members are differentially regulated by different E3 ubiquitin ligases both in the dark and light conditions.…”
Section: Discussionmentioning
confidence: 98%
“…Strikingly, PIF1 directly interacts with COP1 and SPA complex and acts as a cofactor of COP1 E3 ubiquitin ligase to synergistically degrade the positively acting factor HY5 to repress photomorphogenesis in the dark 7 . PIFs also interact with DET1 and synergistically repress photomorphogenesis in the dark 8 . Therefore, the COP/DET/SPA and PIF complexes act independently as well as synergistically to prevent seed germination and seedling emergence in the dark.…”
mentioning
confidence: 99%
“…3) and stabilizes PIFs. Strikingly, the degradation of PIFs in the det1 background is not mediated by the 26S proteasome pathway, as the inhibitors of the 26S proteasome failed to block PIF degradation in the det1 background (Dong et al, 2014). Further studies are In the dark, DET1 interacts with PIFs and stabilizes them by an unknown mechanism.…”
Section: Factors Controlling Pif Abundance Under Darknessmentioning
confidence: 99%